Evaluation of Apoptosis-Inducing Coumarins Isolated from Peucedanum japonicum Roots: The Potential for Leukemia Treatment via the Mitochondria-Mediated Pathway - Kyung-Yun Kang; Sonny C. Ramos; Sung-Ju Lee; Sang-Jip Nam; Jong-Jin Kim (Cells)
Inducing programmed cell death in tumors is a fundamental approach in cancer therapy, prompting extensive efforts to discover bioactive compounds with anticancer properties. Peucedanum japonicum, a plant used in traditional medicine across East Asia, has been reported to exhibit various biological activities, including anticancer effects. This study aimed to evaluate the apoptosis-inducing effects of methanol/dichloromethane (MeOH/CH2Cl2) extracts of P. japonicum roots and their components in HL-60 human leukemia cells. Compounds were isolated using solvent extraction and reverse-phase column chromatography, and their structures were confirmed by nuclear magnetic resonance (NMR) spectroscopy. The cytotoxicity effect of the compounds was tested on various cancer cell lines (HL-60, A549, and MCF-7). Two coumarins, (−)-isosamidin (1) and 3′S,4′S-disenecioylkhellactone (2), were isolated through bioactivity-guided fractionation. Compound 2 significantly induced apoptosis in HL-60 cells, as evidenced by an increase in the sub-G1 cell population and the initiation of both early and late apoptosis. Additional apoptotic markers, including reduced mitochondrial membrane potential (MMP) and increased cleavage of caspase-3, -8, and -9, were observed. These findings suggest that compound 2 shows potential as a candidate for leukemia treatment, providing a promising natural-product-based approach to cancer therapy.